2017
DOI: 10.1016/j.jphs.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the antidiabetic agent pioglitazone on bone metabolism in rats

Abstract: Thiazolidinediones (TZDs) are synthetic peroxisome proliferator-activated receptor gamma (PPARγ) agonists used as therapy for type 2 diabetes. However, clinical studies reported that the therapeutic modulation of PPARγ activity using TZDs may induce negative effects on bone metabolism. This study aimed to evaluate the effect of the TZD pioglitazone on bone metabolism in rats. Male Wistar rats were treated orally with pioglitazone 5 or 20 mg/kg daily for 24 weeks. Bone strength was evaluated using a 3-point ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The overall best combination therapy in controlling blood glucose without reducing calcium bone resorption has been shown in the animal group, which received Bifidobacterium longum and pioglitazone. A previous study showed that pioglitazone treatment did not affect serum calcium levels [37]. Similarly, no changes in serum calcium concentration in the pioglitazone group compared to the control group were found.…”
Section: Discussionmentioning
confidence: 78%
“…The overall best combination therapy in controlling blood glucose without reducing calcium bone resorption has been shown in the animal group, which received Bifidobacterium longum and pioglitazone. A previous study showed that pioglitazone treatment did not affect serum calcium levels [37]. Similarly, no changes in serum calcium concentration in the pioglitazone group compared to the control group were found.…”
Section: Discussionmentioning
confidence: 78%
“…134 Studies in rodents exposed to pioglitazone have found either no adverse effects on bone 142,205 or negative effects. Several studies found that pioglitazone resulted in decreases in BMD, 199,202,206 decreased bone strength, 199,207 decreased osteoblast surface and mineralizing surface, and increased osteoclast surface and number, 199 supporting that pioglitazone suppresses bone formation and promotes bone resorption, 207 predisposing to bone fragility. These effects have been reversible in certain studies 206,207 with discontinuation of treatment.…”
Section: Skeletal Effects: In Vivomentioning
confidence: 99%
“…Recently, several other drugs were also clearly shown to cause bone fragility. We have previously reported the effects of antidiabetic (11) and antiepileptic (12,13) agents on bone metabolism; these led to enhanced bone fragility. The present study investigates the effects of calcineurin inhibitors, which are immunosuppressants that have greatly contributed to the advancement of transplant therapy in recent years, on bone metabolism.…”
mentioning
confidence: 99%